2008
DOI: 10.1210/en.2008-1235
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Potent Phytoestrogen Glycinol in Elicited Soybean (Glycine max)

Abstract: The primary induced isoflavones in soybean, the glyceollins, have been shown to be potent estrogen antagonists in vitro and in vivo. The discovery of the glyceollins' ability to inhibit cancer cell proliferation has led to the analysis of estrogenic activities of other induced isoflavones. In this study, we investigated a novel isoflavone, glycinol, a precursor to glyceollin that is produced in elicited soy. Sensitive and specific in vitro bioassays were used to determine that glycinol exhibits potent estrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…It is interesting to note that in our previous publication, we investigated a novel isoflavone, glycinol, a precursor to glyceollin that is produced in elicited soy, and we found it to be a potent phytoestrogen (Boue et al, 2009). In the current study, we demonstrate that glyceollin I is the most potent, antiestrogenic isomer of the glyceollin mixture and is distinctly different from its estrogenic precursor glycinol (Boué et al, 2009).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…It is interesting to note that in our previous publication, we investigated a novel isoflavone, glycinol, a precursor to glyceollin that is produced in elicited soy, and we found it to be a potent phytoestrogen (Boue et al, 2009). In the current study, we demonstrate that glyceollin I is the most potent, antiestrogenic isomer of the glyceollin mixture and is distinctly different from its estrogenic precursor glycinol (Boué et al, 2009).…”
mentioning
confidence: 49%
“…3 (Banks and Dewick, 1983). Glycinol, which we have shown previously to be estrogenic (Boué et al, 2009), is derived from daidzein via a pterocarpan by cyclization and 6␣-hydroxylation with retention of configuration (Banks and Dewick, 1983;Hagmann et al, 1984). For the synthesis of the glyceollins, glycinol is prenylated to produce glyceollidin I and II, followed by cyclization into the corresponding glyceollins (Zä hringer et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In Western countries, soy is used as a healthy functional food for postmenopausal women. Many researchers have reported that soybean, isoflavones, glycinol, and soyasaponins exhibit estrogenic activity (Tham et al, 1998;Rowlands et al, 2002;Lehmann et al, 2005;Park et al, 2006;Boué et al, 2009;Cederroth and Nef, 2009). The isoflavones also activate estrogen-responsive genes and regulate the growth of human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Soy foods contain bioactive components other than GEN that have been linked to cancer protection (Boué et al 2009;Wang et al 2008;Zhou et al 2002). Lunasin (LUN) is a 43-amino acid peptide component of post-translationally processed 2S albumin, initially identified in soybeans (Galvez and de Lumen 1999) and also present in barley, wheat and other seeds (Jeong et al 2007(Jeong et al , 2010Silva-Sanchez et al 2008).…”
Section: Introductionmentioning
confidence: 99%